Acellular foreskin dermal matrix is efficient in supporting the growth of urothelial cells derived from hypospadias patients - Cao, Zhiqing; Yang, Zhenwei; Ye, Qunfang; Xiong, Juntan; Zhu, Aozhou (Frontiers in Pediatrics, 2025)
IntroductionHypospadias is a common congenital defect in males, with surgery remaining the primary treatment option. However, urethral reconstruction procedures often require additional tissue transplantation, which is limited by the availability of suitable tissue sources.MethodsIn this study, we prepared acellular dermal matrix (ADM) from foreskin obtained through circumcision and isolated urothelium-derived cells from patients with hypospadias. We then evaluated the growth of these urothelium-derived cells on the ADM.ResultsOur results confirmed successful decellularization of the foreskin dermal tissues and demonstrated that the resulting ADM exhibited minimal cytotoxicity toward primary urothelium-derived cells. CFSE and CCK-8 staining assays revealed robust urothelial cell growth on the ADM. Furthermore, the ADM with growing urothelium-derived cells displayed superior biomechanical properties compared to native ADM, suggesting that foreskin ADM is an excellent scaffold for urothelial cell growth.DiscussionThese findings indicate that foreskin ADM is a promising alternative material for tissue engineering in the treatment of conditions like hypospadias that require urethral reconstruction.